A study of sex/age ratios in wild ungulate populations : an approach to designing an appropriate sampling strategy for estimating the structure of wild ungulate populations on Rooipoort Nature Reserve - Laubscher, Sarah-Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.